Covid-19 and the Brazilian Reality: The Role of Favelas in Combating the Pandemic - Fernandes, Luana Almeida de Carvalho; Silva, Caíque Azael Ferreira da; Dameda, Cristiane; Bicalho, Pedro Paulo Gastalho de (Frontiers in Sociology, 2020)
The consequences of coronavirus in favelas in Rio de Janeiro (Brazil) point to social inequality as a structuring factor in Brazilian society. The contagion spread and multiple death cases reveal the multiplicity of existence ways that cohabit the urban context, indicating that in many of these scenarios, access to decent housing, drinking water and minimum income is not a reality and recommendations from international health agencies are challenging to implement. Against government technopolitics that drive different forms of death to the poorest, black communities and slum dwellers, territorial insurgencies indicate other paths for the construction of a dignified life and access to fundamental rights, targeted solidarity practices, territorial political organization and the construction of specific public policies to deal with the effects of the virus which takes into account the particularities and distinct realities of the territory. The experiences of community organization around Crisis Offices in the favelas, led by social organizations and supporting institutions, have guaranteed i) food and personal hygiene items distribution, ii) sanitization of alleys, iii) dissemination of information on the virus and iv) political articulation for disputes in defense of life preservation in the favelas, in opposition of genocidal processes carried out by the state power. Such local spaces represent practices of resistance to the death policies undertaken by the state policies, which most are not configured as spaces for collective construction and disregard inequalities and different needs in these territories. That way, community associations are presented as an inflection point, a deviation from the normal course of modulated subjectivities by the social principles and practices of neoliberalism, with the indication that the most efficient way to deal with social crises is through the strengthening of the collective and the popular organizations.